ANTIBACTERIAL EFFECTIVENESS OF KECAPI SENTUL EXTRACT (SANDORICUM KOETJAPE MERR.) AGAINST STREPTOCOCCUS MUTANS - Adhimas Rilo Pambudi; Yusrinie Wasiaturrahmah; Didit Aspriyanto (ODONTO : Dental Journal, 2021)
ABSTRACTBackground: One of the causing dental caries is a microorganism, namely Streptococcus mutans. Kecapi sentul leaves extract (Sandoricum koetjape Merr.) contain alkaloid, flavonoid, saponin, steroid, phenol, and triterpenoid which have antibacterial properties on the inhibition Streptococcus mutans which has the potential to prevent dental caries.Method: This research uses a laboratory experimental design with a post-test control group only design, using seven treatment groups, namely kecapi sentul leaves extract with the concentration of group 30%, 40%, 50%, 60%, 70%, Chlorhexidine gluconate 0.2% as positive control and aquadest as negative control were repeated 4 times. Result: Non parametric test Kruskal Wallis and Post Hoc Mann Whitney methods showed that each treatment group was significantly different in the diameter of the formed inhibition zone. The mean diameter of the inhibition zone with a concentration of 30% was 9.1 mm, 40% was 13.3 mm, 50% was 17.13 mm, 60% was 18.65 mm and 70% was 21.05 mm.Conclusion: Kecapi sentul leaves extract (Sandoricum koetjape Merr.) with the concentration of group 30%, 40%, 50%, 60% and 70% have antibacterial potential against the growth of Streptococcus mutans.